Active subspace approach to reliability and safety assessments of small satellite separation. (February 2017) - Hu, Xingzhi; Chen, Xiaoqian; Zhao, Yong; Tuo, Zhouhui; Yao, Wen
Abstract: Ever-increasing launch of small satellites demands an effective and efficient computer-aided analysis approach to shorten the ground test cycle and save the economic cost. However, the multiple influencing factors hamper the efficiency and accuracy of separation reliability assessment. In this study, a novel evaluation approach based on active subspace identification and response surface construction is established and verified. The formulation of small satellite separation is firstly derived, including equations of motion, separation and gravity forces, and quantity of interest. The active subspace reduces the dimension of uncertain inputs with minimum precision loss and a 4th degree multivariate polynomial regression (MPR) using cross validation is hand-coded for the propagation and error analysis. A common spring separation of small satellites is employed to demonstrate the accuracy and efficiency of the approach, which exhibits its potential use in widely existing needs of satellite separation analysis. Highlights: An active subspace approach is employed for separation reliability assessment. It has considerably high analysis accuracy and efficiency under multiple factors. It can help predict satellite separation performance and simplify the ground test.